2016
DOI: 10.1155/2016/8693278
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparison of the Performance of Autogenous Brachial-Basilic Transposition Arteriovenous Fistula and Prosthetic Forearm Loop Arteriovenous Graft in a Multiethnic Asian Hemodialysis Population

Abstract: Aim. For patients who have exhausted cephalic vein arteriovenous fistula (AVF) options, controversy exists on whether brachial-basilic AVF with transposition (BBTAVF) or a forearm arteriovenous graft (AVG) should be the next vascular access of choice. This study compared the outcomes of these two modalities. Methods. A retrospective study of 122 Asian multiethnic patients who underwent either a BBTAVF (81) or an AVG (41). Maturation time and intervention rates were analyzed. Functional primary, secondary, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…This can improve vasospasm of the radial artery, increase blood flow of an internal fistula, and promote maturation of an internal fistula. 31,32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can improve vasospasm of the radial artery, increase blood flow of an internal fistula, and promote maturation of an internal fistula. 31,32…”
Section: Discussionmentioning
confidence: 99%
“…Chue et al. 32 showed that, in patients with ESRD, BPS was inferior to CL in delaying the time to first on-study VTE (HR 1.43; P = 0.001). However, Coleman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the main outcomes reported in various studies. 42 , 46 62 ) Chemla and Morsy found that TBBAVF offered a better patency rate with greater cost-effectiveness compared with brachio-axillary AVG. 53 ) Chue et al studied 122 Asian patients and reported that TBBAVF provided superior patency and required fewer salvage interventions compared with forearm AVG.…”
Section: Tbbavf Vs Avgmentioning
confidence: 99%
“… 53 ) Chue et al studied 122 Asian patients and reported that TBBAVF provided superior patency and required fewer salvage interventions compared with forearm AVG. 62 ) However, recent studies showed comparable patency between AVG and TBBAVF and have favored the use of prosthetic grafts in specific groups like elderly patients, because of the short cannulation period. 42 , 55 , 61 ) Overall, utilization of TBBAVF is associated with reduced risk of access failure, whereas AVG represents the preferred option for elderly patients.…”
Section: Tbbavf Vs Avgmentioning
confidence: 99%
“…[6][7][8] When patients are not candidates for wrist AVF, current guidelines recommend upper arm AVF if there is suitable vein; however, this decision of next access is controversial. [9][10][11][12] Currently, arteriovenous grafts (AVGs) are not recommended unless no suitable vein is available. Studies are limited regarding the outcomes of forearm loop arteriovenous graft (flAVG) with respect to their influence on upper arm superficial veins.…”
Section: Introductionmentioning
confidence: 99%